Clinical effect of hyperbaric oxygen therapy in adhesive postoperative small bowel obstruction. Issue 4 (3rd February 2014) - Fukami, Y; Kurumiya, Y; Mizuno, K; Sekoguchi, E; Kobayashi, S
Abstract: Background: Hyperbaric oxygen (HBO) therapy is a controversial treatment for adhesive postoperative small bowel obstruction, with only a few small studies reported. The aim of this study was to assess the clinical value of HBO therapy in the treatment of adhesive postoperative small bowel obstruction. Methods: Between April 2006 and March 2012, all patients with adhesive postoperative small bowel obstruction were treated using either decompression therapy or HBO. Patients undergoing HBO therapy were treated once a day at a pressure of 2·0 atmospheres absolute and received 100 per cent oxygen. Patients showing no clinical and radiological improvement with HBO therapy were converted to decompression therapy by means of a long tube. Medical records were reviewed and outcomes analysed. Results: A total of 305 patients were treated, of whom 142 underwent tube decompression therapy during the first 3 years and the remaining 163 had HBO therapy during the last 3 years. The median number of HBO treatments was 3 (range 1–7). A total of 143 patients (87·7 per cent) were treated successfully with HBO without long-tube decompression. HBO therapy was associated with earlier resumption of oral intake (mean 4·7 versus 6·5 days; P = 0·001) and a shorter hospital stay (mean 10·3 versus 14·1 days; P = 0·001). The rate of operation was 7·4 per cent in the HBO group and 14·8 per cent in group treated by decompression alone ( P = 0·037). Conclusion: In this study, HBO therapy was safe for the treatment of adhesive postoperative small bowel obstruction. It reduced the need for surgery and time to recovery as well as the hospital stay. Abstract : May avoid surgery in small bowel obstruction